Tunisia: Agriculture Support Services Project - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Agriculture Support Services Project is supporting, on a pilot basis, public, cooperative, and private organizations that deliver services for livestock producers.